Effect of Age on Job Satisfaction and Emotional Exhaustion of Primary School Teachers in Greece - Sophia Anastasiou; Evaggelos Belios (MDPI AG, 2020)
The level of occupational burnout (OB) and job satisfaction (JS) was investigated in primary school teachers (n = 125) in the region of Epirus in Northwestern Greece. Teachers exhibited a high level of emotional exhaustion (EE), a medium level of depersonalization (DP), and a lack of personal accomplishment (PA). In our study, EE, which is a significant component of OB, varied according to intrinsic and extrinsic JS parameters. Teachers were less satisfied and more stressed with extrinsic job characteristics of their job, such as working conditions and working hours. Female teachers were more likely to exhibit increased satisfaction from intrinsic job characteristics, whereas male teachers were more likely to exhibit increased emotional exhaustion and lack of personal accomplishment. Job satisfaction had a significant negative impact on emotional exhaustion. Job satisfaction accounted (EE = 47.173 − 3.527*JS) for 35.1% of the total variation in the dependent variation of EE (F(1124) = 66.094, p < 0.001), indicating that job satisfaction had a significant negative effect on EE, such that an additional unit in job satisfaction will lower EE by 3.527. A Pearson correlation analysis revealed that age correlated negatively with emotional exhaustion (r = −0.204, p = 0.023). Proactive human resources policies may be required to protect the newly hired and less experienced teachers from exposure to stressful working conditions.